Effects of short‐term mindfulness‐based training on executive function: Divergent but promising. (29th May 2020) - Zhou, Honggui; Liu, Hong; Deng, Yunlong
Abstract: Mindfulness‐based training (MBT) has repeatedly been proven effective in improving mental health, as well as in eliciting advantages in executive functions (EFs), as demonstrated by objective measures. However, few studies have discussed the role MBT plays in increasing EFs over short periods of time. This current review, to our knowledge, is the first study to investigate the effect of short‐term MBT on EFs. In this case, 14 studies were eventually included after literature screening using PubMed, MEDLINE, Elsevier, Embase, EBSCO and references from retrieved articles. We found that the relationship between short‐term MBT and three main components of EFs were found controversial. Some reported that individuals' inhibition, working memory and attention shifting were significantly improved by short‐term MBT, whereas others reported no such strong connections between MBT and EFs. These controversial findings result from the use of varied assessment instruments, cognitive tasks and experimental materials. Nonetheless, the findings from this review suggest short‐term MBT could be of great value in improving mental health, which might especially enable the enhancement of individuals' inhibition and updating subfunctions of EFs. These practical evidences could have a strong impact on clinical psychology. However, the lack of consistency across the studies in this review indicated that more standardized and profound studies exploring the effects of short‐term MBT on EFs are needed in the future.